2018
DOI: 10.20546/ijcmas.2018.710.122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth, Physiological Aspects and Yield of Cabbage (Brassica oleracea L. cv Rareball) in Knolkhol and Broad Bean Intercropping System under Imphal West Condition

Abstract: An investigation was carried out to study the effect of intercropping crops (knol khol and broad bean) on growth, physiological aspects and yield of Cabbage. Sole crop of Cabbage was grown and between the inter-row spaces knol khol/broad bean was intercropped in single/double row planting. Spacing of 60 x 30 cm between cabbage and 30 x 30 cm for knol khol and 30 x 20 cm for broad bean was adopted. Growth parameters were recorded for cabbage as sole crop and as intercropped with single/double row of knol khol /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…It is widely reported that in most cases the main crop in an intercropping system does not perform as well as it should as in monoculture and does not reach as high a yield level due to an increased competition among intercropped plants for light, soil nutrients and water (Willey, 1979). Similar reports by Ananda et al, (2018) reported reduced performance of cabbage as intercrop which might be owned to the fact that sole cropped cabbage showed better performance in terms harvest index, net assimilation rate, plant growth efficiency, crop growth rate and relative growth rate. Poor performance of intercropped cabbage for these attributes may have caused negative impact on the yield parameters of cabbage as an intercrop.…”
Section: Yield Parameterssupporting
confidence: 69%
See 1 more Smart Citation
“…It is widely reported that in most cases the main crop in an intercropping system does not perform as well as it should as in monoculture and does not reach as high a yield level due to an increased competition among intercropped plants for light, soil nutrients and water (Willey, 1979). Similar reports by Ananda et al, (2018) reported reduced performance of cabbage as intercrop which might be owned to the fact that sole cropped cabbage showed better performance in terms harvest index, net assimilation rate, plant growth efficiency, crop growth rate and relative growth rate. Poor performance of intercropped cabbage for these attributes may have caused negative impact on the yield parameters of cabbage as an intercrop.…”
Section: Yield Parameterssupporting
confidence: 69%
“…Intercropping did not produce a pronounced effect on the total dry matter of cabbage head (Table 2) which are in confrontation with the studies by Ananda et al, (2018) who reported that the dry matter was maximum in cabbage grown as sole crop.…”
Section: Growth Parameterssupporting
confidence: 55%
“…Analysis of economics (B:C ratio) had shown that the highest returns were obtained with cabbage in combination with intercrops Mawnai et al (2021). Moreover, it was also noticed that the weight of the cabbage head was significantly influenced by intercropping (Ananda et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The polar and equatorial diameter of the head were measured, as well as the head circumference. The Compactness of the head is measured in terms of the 'Z' value by using the following formula shown below (Bhat et al, 2017), and the harvest index was calculated as the ratio of net head weight to gross head weight (Ananda et al, 2018). Net head weight was measured by collecting five heads separately and weighing them, and the yield per plot and yield per hectare were calculated accordingly.…”
Section: Yield Parametersmentioning
confidence: 99%